Dysfunctional Curriculum: creating the battles against capitalism - Steferson Zanoni Roseiro; Sandra Kretli da Silva (Universidade Federal do Rio Grande do Sul, 2018)
Starting on the premise of a functional Capitalism that is not afraid of rejecting its own ideas to reassure itself as an overcoding machine, this essay points to the curricular practices in the production of pauses based on a philosophy of error. If, in a functional regime, it is expected from school an endless curricular functionalism, betting on school and on its curricular exercises may produce some kind of voids on the functionalism sense. It was an interventional research based on the networks conversations performed with teachers in public school of Vitória/ES. As results, teachers show moments of rupture with the functional regime while they inquire how to proceed and, thus, they create, in immanence, dysfunctional curricula.